Gender and identity in Mandarin Chinese blogosphere - Siqun, Xu (My University, 2007)
The research on gender and identity in Mandarin Chinese CMC sphere has been less explored from a sociolinguistic point of view, which motivates me to do some relevant studies to shed light on the issues of gender difference and online identity in Mandarin Chinese blogosphere. In this project, both postmodern view of gender and poststructural perspective on language and identity were employed as theoretical basis. Chinese bloggers’ gender differences and identities were examined from two main aspects: topic selections and specific features. Each aspect consists of five concrete and purposely-selected dependent variables, all of which were quantitatively analysed with individual qualitative explanation. The statistical results suggest on one hand that no reliable gender differences appear in Mandarin Chinese blogosphere by analysing specific features, such as Chinese sentence final particles, figures of speech and so on. On the other hand, significant gender differences appeared in most of the sub type topics. That is, both genders in modern China begin to construct their discursive online identities by employing different strategies in particular context. Finally, my analysis suggests that diversity of gender differences and online identities construction does not allow us to jump to the conclusion that there is or is not gender difference in Mandarin Chinese blogosphere, which depends on the particular context that online identities locate in and concrete variables that we use to measure. As far as the specific features are concerned, I could suggest that gender neutralization has been a trend in Mandarin Chinese blogosphere.
Keywords: gender; linguistics; Mandarin Chinese; Web 2.0